Association of stress coping self-efficacy and cognitive test anxiety with stress symptomatology in university students - Mur, Julian Andres (2023)
Background: university life is defined by the multiple demands that students face. Exams are events of great concern that can trigger harmful stress responses. The perception of self-efficacy to achieve goals has a modulating effect on cognitive, emotional and behavioral processes. Objective: to analyze the relationship and influence between stress coping self-efficacy, cognitive test anxiety and physical and psychoemotional stress symptomatology in university students in a pandemic context. Method: cross-sectional descriptive-correlational design. 314 university students participated (M = 23, SD = 6.05). Results: significant correlations were found between the variables examined. The proposed model showed that stress coping self-efficacy (efficacy and outcome) and cognitive test anxiety explain 39% physical and psychoemotional stress symptomatology variance. Conclusions: students present greater vulnerability to feelings of anxiety and stress exacerbated by the healthcare context. The study of these variables provides an updated perspective of the psychoemotional interactions that condition the capacity to face university challenges.